2002
DOI: 10.1111/j.2042-7174.2002.tb00591.x
|View full text |Cite
|
Sign up to set email alerts
|

The emergency supply of prescription-only medicines: a survey of requests to community pharmacists and their views on the procedures

Abstract: Objectives — The provisions of the Medicines Act for the emergency supply of prescription‐only medicines (POMs) represent circumstances in which pharmacists in the UK may lawfully supply a patient with a POM without having a prescription. The objectives of this research were to establish the frequency of requests for emergency supplies from doctors and patients, and the characteristics of the requests, to investigate the procedures for emergency supply from the perspective of community pharmacists and to surve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 1 publication
0
13
0
Order By: Relevance
“…A 1998 survey of CPs by O'Neill et al 3 demonstrated that requests for emergency supplies and medicine loans were being made on a frequent basis: at least monthly for three-quarters of respondents, at least weekly for half, and at least daily for 1 in 10. Respondents perceived emergency supplies as an important service, but over three-quarters felt it was open to misuse.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A 1998 survey of CPs by O'Neill et al 3 demonstrated that requests for emergency supplies and medicine loans were being made on a frequent basis: at least monthly for three-quarters of respondents, at least weekly for half, and at least daily for 1 in 10. Respondents perceived emergency supplies as an important service, but over three-quarters felt it was open to misuse.…”
Section: Introductionmentioning
confidence: 99%
“…12–14 A review of the literature has identified only a few studies that have explored emergency supplies by community pharmacies in depth; the majority were based in the UK. 3–8 Moreover, there is a need for a holistic examination, incorporating multiple viewpoints, of how the emergency supply service at community pharmacies may best fit within current and established health and social care provision in order to best support patient care. This evaluation aims to describe the current profile of emergency supply activity in community pharmacies to explore and inform future practice.…”
Section: Introductionmentioning
confidence: 99%
“…The most striking characteristics associated with the patients who had a tider that we identified included having been older, male, a Medicare beneficiary, and having had a previous tider dispensing and a higher burden of chronic disease. O’Neil and colleagues reported that elderly patients most frequently requested an emergency supply of a prescription medication 5. Similarly, Morecroft and colleagues reported that older patients more frequently requested an emergency supply of a prescription medication 4.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, tiders were more likely to be dispensed on a weekend. O’Neil and colleagues reported that patients most commonly requested an emergency supply of respiratory, cardiovascular, and central nervous system medications 5. Morecroft and colleagues reported that patients most commonly requested an emergency supply of cardiovascular, respiratory, and endocrine medications and a high proportion of requests around the weekend 4.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation